KONFLIK TANAH ANTARA PT. FAJAR BAIZURY DENGAN MASYARAKAT DESA COT RAMBONG KECAMATAN KUALA PESISIR KABUPATEN NAGAN RAYA (1996-2015) - Deno Pangestu; Anwar Yoesoef; Zainal Abidin (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2018)
ABSTRACT Conflict is a dispute between individuals and individuals, individuals with groups and groups with groups. Conflict in this research belong to conflict between group that is land conflict between PT. Fajar Baizury with the people of Cot Rambong Village, Kuala Pesisir District, Nagan Raya District, 1996-2015. The purpose of this study is (1) Describe the factors causing the community conflict Cot Rambong Village with PT. Fajar Baizury in Kuala Pesisir Sub-district, Nagan Raya District, (2) Describes the process of conflict, (3) Describe the role of the Government in resolving conflict and (4) Explain the impact of community land conflicts Cot Rambong Village with PT. Fajar Baizury in Kuala Pesisir Sub-district, Nagan Raya District. This research uses qualitative approach with historical method. By the procedure or step of the theme selection work, heuristic/collecting sources, source verification/criticism, interpretation/interpretation of sources and historiography. Using data collection techniques such as interviews, documentation, observation, and literature study. Based on the research results can be seen that (1) This conflict is caused by the conquest of plantation land due to PT. Fajar Baizury annexed community-owned land and the absence of channeling Corporate Social Responsibility (CSR) funds from the company to the public, (2) The course of this conflict is evident several times as in 2014 involving the Legal Aid Institute (LBH), the police and government apparatus including Teuku Umar University students. Year 2015 which is marked by the action of the community demands the rejection of land acquisition for PT. Fajar Baizury. In 2016 the conflict occurred in the form of blocking of garden road owned by PT. Fajar Baizury and the year 2017 marked by the action of the installation of the limitation of Right of Use (HGU) PT. Fajar Baizury, (3) Local Government has played an important role in the settlement such as freeing the captive of the conflict and being a facilitator in the conflict, and (4) The impact of conflict is the lateness of the livelihood, the loss for PT. Fajar Baizury due to inhibition of activities due to lack of full support by local communities and including losses on funding aspects.Keywords: Land Conflict, PT. Fajar Baizury, Cot Rambong Village Society.